Jokha al-Harthi’s Stories - Kitaeva, Nedelya (Sledva : NBU Journal of Humanities and Arts, 2020)
Short introduction to Jokha al-Harthi, her writing and the cultural context she comes from by the translator, Dr. Nedelya Kitaeva, who is teaching Arabic language and Culture at the New Bulgarian University.